Analysis of Service Quality Levels for Social Security Administrator (BPJS) Participants and non-BPJS (Case Study of Ofa Padang Mahondang Village) - Tambunan, Elya Ramadhani; Zainarti, Zainarti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Public service is an important service and is a top priority for administrators to meet the basic needs of society. Basically, the health sector is one of the first-level facilities for Social Security Administrator (BPJS) participants managed at the Public Health Center (Puskesmas). Therefore, the benefits of Puskesmas services are felt and help the community, including BPJS patients, so that the services provided to patients must be of quality according to the specified service standards. This research was conducted with the aim of comparing the quality of service for BPJS and non-BPJS participants as well as the supporting and inhibiting factors of service. Researchers use qualitative research by understanding the research subject. Source of data obtained from secondary and primary data. Furthermore, data collection techniques by conducting observations, interviews, and documentation at the health center, and determination of respondents using snowball sampling, then analyzed using the Miles and Huberman model. To test the level of confidence in the data uses triangulation techniques. The results of the study stated that the quality of services provided to BPJS and Non-BPJS patients at the Ofa Padang Mahondang Health Center was good and in accordance with the needs of the community seen from direct evidence, reliability, responsiveness, assurance, and empathy. While the supporting factors for service are the attitude of employees who are friendly, courteous, flow simplicity and affordable costs, there are still things that need to be improved, namely the lack of supporting facilities and infrastructure, such as loudspeakers, the wifi network is slow and the number of patients who are busy with the number of officers is incompatibility.